2018
DOI: 10.1371/journal.pone.0199627
|View full text |Cite|
|
Sign up to set email alerts
|

Vibrotactile information improves proprioceptive reaching target localization

Abstract: When pointing to parts of our own body (e.g., the opposite index finger), the position of the target is derived from proprioceptive signals. Consistent with the principles of multisensory integration, it has been found that participants better matched the position of their index finger when they also had visual cues about its location. Unlike vision, touch may not provide additional information about finger position in space, since fingertip tactile information theoretically remains the same irrespective of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…First, it is well established that humans rely on somatosensory signals from both their moving and target hands during somatosensory-guided reaching 45 . In addition, tactile input from the unseen target hand improves reaching performance 46 , 47 . Here we show that somatosensory enhancement varies in strength throughout the movement, presumably to facilitate movement guidance to the target hand.…”
Section: Discussionmentioning
confidence: 99%
“…First, it is well established that humans rely on somatosensory signals from both their moving and target hands during somatosensory-guided reaching 45 . In addition, tactile input from the unseen target hand improves reaching performance 46 , 47 . Here we show that somatosensory enhancement varies in strength throughout the movement, presumably to facilitate movement guidance to the target hand.…”
Section: Discussionmentioning
confidence: 99%
“…For the two-point discrimination task, it was reported that two-and six-hour tactile stimulation reduced the twopoint discrimination threshold while reducing the stimulation time to 30 min could not improve the two-point discrimination (13). For proprioceptive localization, the tactile stimulation of the left index finger at frequencies of 30 and 300 Hz for 1,000 ms seems to have improving effects (22). The results of our study demonstrated that 30-min tactile stimulation at the frequency of 16 Hz seemed to be appropriate for improving hand mental rotation in young healthy adults.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that the tactile stimulation could improve two-point discrimination ability in humans (13,14). Mikula et al reported that the tactile stimulation of the left index finger before the right-hand movement could better determine the spatial position of the left finger and that the movement of the right hand towards the left index finger was dealt with more accurately when the left finger was invisible (22). In addition, it was reported that the tactile stimulation could increase the primary motor cortex excitability during mental imagery (18).…”
Section: Discussionmentioning
confidence: 99%
“…Much of our knowledge on the control of pointing movements to regions of our body (hereafter named proprioceptive targets) comes from studies in which subjects had to indicate with the index finger different positions on their contralateral arm hidden from view [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%